Magnetic bio-nanocomposite catalysts of CoFe2O4/hydroxyapatite-lipase for enantioselective synthesis provide a framework for enzyme recovery and reuse - Saire-Saire S. (2020)
Enzymatic catalysis is a sustainable alternative for cost-prohibitive catalysts based on noble metals and rare earths. Enzymes can catalyze selective reactions under mild conditions. Enzyme recovery after a reaction for its reuse is still a challenge for industrial application. Herein, a biocompatible magnetic nanocomposite is presented as alternative for enzyme stabilization and easy recovery. The magnetic core of CoFe2O4 provides capabilities for magnetic recovery. Two different functionalization methods based on adsorption of enzyme onto biocompatible hydroxyapatite (HAP) and through covalent bonding using a molecular spacer based on 3-Aminopropyl)triethoxysilane (APTES) have been evaluated. Both enzymatic bio-nanocomposites presented high selectivity for the transesterification reaction of racemic mixtures of (R,S)-1-phenylethanol, with complete conversion of (R)-1-phenylethanol enantiomer. Studies with different solvent and temperature had demonstrated high range of operation conditions due to enzyme stabilization provided by surface attachment. Meanwhile, magnetic properties allowed easy recovery through application of an external magnetic field for enzyme reuse. Results showed high stability of lipase covalently bond to CoFe2O4/HAP over several reaction cycles.